2016
DOI: 10.3762/bjoc.12.238
|View full text |Cite
|
Sign up to set email alerts
|

Protonated paramagnetic redox forms of di-o-quinone bridged with p-phenylene-extended TTF: A EPR spectroscopy study

Abstract: The chemical oxidation and reduction processes of deprotonated, direduced o-quinone-exTTF-o-quinone in protic solvents were studied by EPR spectroscopy. The formation of relatively stable paramagnetic protonated redox forms of the parent triad was very surprising. The character of spin-density distribution in the semiquinone–quinone and semiquinone–catechol redox forms indicates that the p-phenylene-extended tetrathiafulvalene connector provides a quite effective electronic communication channel between dioxol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The value of the antiferromagnetic coupling between the two semiquinone radical centers was estimated as 1092 cm −1 [23]. Consequently the biradical triad L is Electronic Paramagnetic Resonance (EPR) silent [23].…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…The value of the antiferromagnetic coupling between the two semiquinone radical centers was estimated as 1092 cm −1 [23]. Consequently the biradical triad L is Electronic Paramagnetic Resonance (EPR) silent [23].…”
Section: Synthesismentioning
confidence: 99%
“…This triad was previously studied by open-shell density functional theory calculations, which revealed that the broken-symmetry (BS) state in a global minimum is singlet biradical according to the spin density distribution. The value of the antiferromagnetic coupling between the two semiquinone radical centers was estimated as 1092 cm −1 [23]. Consequently the biradical triad L is Electronic Paramagnetic Resonance (EPR) silent [23].…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Interaction of 68 with an excess of Mn 2 (CO) 10 results in subsequent formation of semiquinonate 69 and then the trinuclear species 70 (Scheme 30) [42]. Mononuclear semiquinonate 69 has a sextet lines EPR spectrum in toluene due to splitting of the unpaired electron on the 55 Mn nucleus (Figure 3a). A multiplet spectrum that arises upon further reduction of 69 with Mn 2 (CO) 10 was attributed to the trinuclear species 70.…”
Section: Ss~oo Systemsmentioning
confidence: 99%
“…Mononuclear semiquinonate 69 has a sextet lines EPR spectrum in toluene due to splitting of the unpaired electron on the 55 Mn nucleus (Figure 3a). A multiplet spectrum that arises upon further reduction of 69 with Mn2(CO)10 was attributed to the trinuclear species 70.…”
Section: Ss~oo Systemsmentioning
confidence: 99%